LOCAL WISDOM-BASED CHARACTER BUILDING THROUGH SOCIAL SCIENCE LEARNING IN ELEMENTARY SCHOOLS - Felia Siska; Sapriya Sapriya; Trina Febriani (Jurnal Ilmu Sosial Mamangan, 2021)
This study was motivated by globalization progress, causing the Indonesian people to lose national character and leave local wisdom from generation to generation. Therefore, it is necessary to have character building for students amidst technological advances so that the character traits of students can be applied in everyday life. One of the learning activities with character education is a social science, especially at the elementary school level. This study aimed to analyze the local wisdom-based character building through social science learning in elementary schools. This study used a qualitative approach with a library research method. Based on the results, the local wisdom-based character education through social science learning in elementary schools had to apply 18 character traits defined by the Ministry of Education and Culture. Elementary schools include local wisdom values in their learning plans and apply them to thematic learning.